Canada : Financial Sector Assessment Program-Technical Note-Oversight of Financial Market Infrastructures and Fintech Development. (IMF Staff Country Reports; Country Report ;, 2020)
This paper reviews assessment of financial market infrastructures (FMIs) and authorities' responsibilities in Canada. The report shows that the FMIs have operated normally under a well-established legal and oversight framework that is distinct for Canada. The Bank of Canada (BOC) has issued a Guideline that defines the criteria for identifying FMIs. Recognition of a clearing agency is also required under provincial securities legislation where terms and conditions and the clearing rule would apply. The current oversight approach can benefit from stronger enforcement powers available to the BOC. Provincial securities regulators are encouraged to train FMI oversight staff in advanced quantitative skills to support risk assessment. Further enhancement in managing liquidity and operational risks will help ensure the robust functioning of FMIs. Improvements in cyber resiliency continue in line with international guidance, including industry-wide exercises carried out by FMI operators and participants. However, compliance to endpoint security needs to be tightened by self-attestations and audits of FMI participants. The categorization and reporting of operational incident severity levels could be further coordinated.